Morality Meters and Their Impacts on Moral Choices in Videogames: A Qualitative Study. Issue 1 (January 2022) - Formosa, Paul; Ryan, Malcolm; Howarth, Stephanie; Messer, Jane; McEwan, Mitchell
Morality meters are a commonly used mechanic in many ethically notable video games. However, there have been several theoretical critiques of such meters, including that people can find them alienating, they can instrumentalise morality, and they reduce morality to a binary of good and evil with no room for complexity. While there has been much theoretical discussion of these issues, there has been far less empirical investigation. We address this gap through a qualitative study that involved participants playing a custom-built visual novel game ( The Great Fire ) with different intuitive and counter-intuitive morality meter settings. Overall, we found that players' attitudes towards the morality meter in this game was complex, context sensitive and variable throughout gameplay and that the intuitiveness of the meter encouraged participants to treat the meter more 'as a moral guide' that prompts reflection and less 'as a score' to be engaged with reactively.